2016
DOI: 10.1038/srep27338
|View full text |Cite
|
Sign up to set email alerts
|

A method for measuring rotation of a thermal carbon nanomotor using centrifugal effect

Abstract: A thermal nanomotor is relatively easy to fabricate and regulate as it contains just a few or even no accessory devices. Since the double-wall carbon nanotube (CNT)-based rotary nanomotor was established in a thermostat, assessment of the rotation of the rotor (inner tube) in the stator (outer tube) of the nanomotor has been critical, but remains challenging due to two factors: the small size of the rotor (only a few nanometers) and the high rotational frequency (»1 GHz). To measure the rotation of the nanomot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…For example, Cai et al have proposed to use the centrifugal effect to measure the high-speed rotation of a thermal carbon nanomotor. 10 Recently, Liu et al have systematically developed the real-time optical imaging and broadband in situ spectroscopy, and have studied the optical absorption spectrum of various types of CNTs. [11][12][13] Their experimental results revealed that the interaction between two individual tubes can significantly modify the optical transition energy in DWCNTs.…”
mentioning
confidence: 99%
“…For example, Cai et al have proposed to use the centrifugal effect to measure the high-speed rotation of a thermal carbon nanomotor. 10 Recently, Liu et al have systematically developed the real-time optical imaging and broadband in situ spectroscopy, and have studied the optical absorption spectrum of various types of CNTs. [11][12][13] Their experimental results revealed that the interaction between two individual tubes can significantly modify the optical transition energy in DWCNTs.…”
mentioning
confidence: 99%
“…Muniz et al [ 18 , 19 ] developed twisted bilayer graphene with periodic sp 3 interlayer bonds, and estimated its mechanical properties via molecular dynamics (MD) simulations. Cai et al [ 20 ] introduced a graphene ribbon in a rotor to show the centrifugal force at the nano scale [ 21 , 22 ]. Song et al [ 23 , 24 ] modelled a rotary nanodevice for achieving the transfer of rotation–translation.…”
Section: Introductionmentioning
confidence: 99%
“…In their model, a deformable part (DP) made of graphene was connected to the CNT rotor. The DP deforms when the rotation-induced centrifugal force [36] is strong enough, and the axial translation of the rotor happens simultaneously. Unfortunately, DP may be self-bonded into a narrow ring under high rotational speed, which is unrecoverable and unstable.…”
Section: Introductionmentioning
confidence: 99%